A dél-dunántúli gázellátás története 1869-től napjainkig - Haffner, Tamás (Közép-Európai Közlemények, 2016)
In Hungary gas was used as a public utility, to ensure public lightning in the form of lightning gas. The first gas based public lightning system of the South West Hungary was introduced in Pécs, between 1869 and 1870. Since 1935 the production continued in a new, modern coke factory. The number of the consumers increased after the secularization as well. They wanted to solve the increasing gas shortage with make-do solution, but a final answer was only the natural gas, which appeared late in 1985. By this the city’s gas production ended. In 1964, the gas factories and PB gas services of Fejér, Tolna and Baranya were merged into a company, named Dél-Dunántúli Gázgyártó és Szolgáltató Vállalat (Gas Production and Services Company of South West Hungary -DDGAZ). After the democratic transformation the company were changed into a stock company, and it got privatized in 1996. Later the company – which fell into the hands of the E.ON-Group –, and other members of the group supplied the population of the three county until the end of 2015. In 2016, the state owned Főgáz Rt. (Natural Gas Stock Company) took over the supply of the population, by this the re-secularization of the gas services which was begin in the 1990’s was fulfilled.